STAT1 facilitates oestrogen receptor α transcription and stimulates breast cancer cell proliferation. Issue 12 (17th October 2018) - Hou, Yingxiang; Li, Xin; Li, Qianhua; Xu, Juntao; Yang, Huijie; Xue, Min; Niu, Gang; Zhuo, Shu; Mu, Kun; Wu, Gaosong; Li, Xiumin; Wang, Hui; et al.
Abstract: Oestrogen receptor α (ERα) is overexpressed in two‐thirds of all breast cancer cases and is involved in breast cancer development and progression. Although ERα ‐positive breast cancer can be effectively treated by endocrine therapy, endocrine resistance is an urgent clinical problem. Thus, further understanding of the underlying mechanisms involved in ERα signalling is critical in dealing with endocrine resistance in patients with breast cancer. In the present study, unbiased RNA sequence analysis was conducted between the MCF‐7 and MCF‐7 tamoxifen‐resistant (LCC2) cell lines in order to identify differentially expressed genes. The whole transcriptomic data indicated that the JAK‐STAT pathway is markedly up‐regulated, particularly the ISGF3 complex. As the critical effectors, STAT1 and IRF9 were up‐regulated 5‐ and 20‐fold, respectively, in LCC2 cells. The biological experiments indicated that STAT1 is important for ERα signalling. Depletion of STAT1 or inhibition of STAT1 function significantly decreased levels of ERα protein, ERα ‐target gene expression and cell proliferation in both the MCF‐7 and LCC2 cell lines. Chromatin immunoprecipitation revealed that ERα transcription is associated with STAT1 recruitment to the ERα promoter region, suggesting that transcriptional regulation is one mechanism by which STAT1 regulates ERα mRNA levels and ERα signalling in breast cancer cells. The present study reveals a possible endocrine‐resistant mechanism by which STAT1 modulates ERα signalling and confers tamoxifen resistance. Targeting of STAT1 is a potential treatment strategy for endocrine‐resistant breast cancers.